PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI DENGAN SIKAP MENTAL TERHADAP KEPUASAN KERJA ANGGOTA DIREKTORAT ZENI TNI - AD - Sobari, - (2014)
The purpose of this study is to provide empirical evidence relating to the effects of leadership style and organizational culture on the mental attitude of a member of Engineers Directorate of the Army as well as the influence of leadership style , organizational culture and mental attitude towards the job satisfaction of Engineers Directorate of members of the army. In accordance with the problems in this study , then , the population is all members of the Directorate of Army Engineers , amounting to 300 members . Where the error rate is used by 10 % to as much as 182 samples obtained samples. Based on the results of the study showed significant influences of leadership style on the mental attitude of members of the Directorate of Army Engineers , There is a significant influence of organizational culture on the mental attitude of members of the Directorate of Army Engineers , There is a significant effect of leadership style on job satisfaction of Engineers Directorate of members of the Army , Ther e significant influence of or ganizational culture on job satisfaction of Engineers Directorate of members of the army and the significant influences of mental attitude on job satisfaction of Engineers Directorate of members of the Army